Quercus de M. Colmeiro (1816 - 1901) y J. Gay (1786 - 1864) en el Herbario del Real Colegio de Alfonso XII (San Lorenzo del Escorial, Madrid) - Perea, Domingo; García, Alfonso; Carrasco de Salazar, María Andrea; Martín-blanco, Carlos José (Botanica Complutensis, 1998)
CARRASCO, NI. A., C. J. MARTIN-BLANCO, A. GARCÍA & D. PEREA, 1998. The Quercus of M. Colmeiro(1816-1901) andi. Gay (1786-1864) in rhe Herbarium of the Real Colegio Alfonso XII (San Lorenzo del Escorial, Madrid). BoL Complutensis, 22: 153-171. Several sets of planís, with historic interest have been spotíed in the Real Colegio Alfonso XII, of San Lorenzo del Escorial, Madrid. la Ihis paper we present the study of one of those sets, belonging to the Colmeir&s and Gay's herbaria. Sorne of them are Typus materials (Quercus avellanaeformis Colmeiro & Boutelou, Quercus bellota var. grandifolia Colmeiro & Houtelou and Quercus bellota var. parvifolia Colmeiro & Boutelou).